A two parameter characterization of edge cracked NiTi shape memory alloy under plane strain conditions - Merde, Oğuzhan Fikri. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
Shape memory alloys (SMAs) are metallic systems that exhibit reversible, diffusionless, martensitic phase transformation. Employing finite element analyses, the stress fields and crack tip constraints generated are examined for a NiTi SMA which exhibits superelastic behavior. For this purpose, a single edge cracked configuration satisfying plane strain conditions is subjected to uniform loading. Both pure Mode I and mixed mode (Mode I + Mode II) configurations are elaborated by changing the crack inclination angle. As a novel step, a multi-parameter fracture mechanics approach is adapted to characterize the dependence of stress field components on both asymptotic r−1/2 and radial ro terms around the crack tip. This task is accomplished by generating closed-form fitting expressions for stress components via nonlinear leastsquare regression of the full field data from finite element analyses. It has been shown that ro term plays a significant role on the stress field around the crack tip in NiTi SMAs. In characterization of crack tip constraint in NiTi, stress triaxiality parameter, Q, is utilized in the present work. To quantify the behavior of Q, the material characteristics of NiTi such as transformation start and end stresses, hardening modulus and transformation strain are varied under both pure Mode I and mixed mode configurations. The results show that martensitic transformation has an effect of stress constraint relaxation effect reflected by the decrease of Q parameter. Meanwhile promotion of transformation start stress is found to have a strong contribution in constraining crack tip, the transformation end stress is observed to have negligible effect.
Keywords: Shape memory alloys.; Fracture mechanics.